Centralia High School Alumni Association: establishing a research-based communications plan - Waller, Kristin J. (Kansas State University, 2008)
The goal of this graduate-level report is to establish a research-based communications plan for the Centralia High School Alumni Association (CHSAA) in order to build permanence in relationships between alumni members and the school, as well as, to secure the financial future of the organization. The project will follow a standard public relations RACE (research, action, communication, and evaluation) model. Background research summarizing current trends in the economy, fundraising, donor motivations and solicitation tactics; CHSAA and the environment that surrounds the organization, the school, and businesses in the communities; intervening publics and primary research is analyzed. As a result of the background analysis, four key publics and corresponding strategies and tactics to reach those publics are identified. A campaign budget is proposed; a two-year time period is shown for implementation of created tactics; and finally, evaluation criteria are listed to provide CHSAA with mechanisms for measuring progress toward the end goal of CHSAA being a permanent fixture for Centralia Schools, its alumni members and surrounding communities.
Keywords: communications; RACE model; public relations; high school; fundraising; alumni association; Education, Administration (0514); Mass Communications (0708); Psychology, Social (0451)